One-step synthesis of ferrocenyl glycidyl ethers as combustion catalysts for the thermal decomposition of ammonium perchlorate - Liu, Jinyi; Yu, Haojie; Wang, Li; Vatsadze, Sergey Z.; Chen, Dingning; Wu, Xudong; Gong, Xiaodan; Wang, Yu (Powder technology, 2023)
As an oxidant, the pyrolysis behavior of ammonium perchlorate is the key to the combustion of composite solid propellants. Seeking a suitable catalyst to promote AP decomposition has drawn much attention. Ferrocene-based compounds are often used as burning rate catalysts because of their excellent catalytic effect. However, ferrocene-based burning rate catalysts are prone to migration during storage of propellants. In this study, six ferrocenyl glycidyl ethers were designed and synthesized to improve the anti-migration properties, and the related spectra characterization techniques were adopted to confirm their molecular structures. Furthermore, their related properties and mechanisms were also studied. As a result, they showed good redox performance, positive promotion on AP decomposition, excellent combustion and mechanical performance. Meanwhile, they had a higher anti-migration behavior compared with catocene and ferrocene. This study demonstrates that ferrocenyl glycidyl ethers have great potential to be applied as multifunctional burning rate catalysts in composite solid propellants. [Display omitted] •Six ferrocenyl glycidyl ethers as combustion catalysts were prepared.•The possible catalytic mechanism for AP decomposition was studied.•The possible anti-migration mechanism in CSPs was studied as well.•Ferrocenyl glycidyl ethers showed excellent catalytic effect on AP decomposition.•Ferrocenyl glycidyl ethers showed good combustion and anti-migration performance.